Plankton potential as bioindicator of trophic status of Lokop River Leuser Ecosystem - Andri Yusman Persada; Suri Purnama Febri; Kartika Aprilia Putri; Herlina Putri Endah Sari; Rianjuanda Djamani (Depik, 2022)
Lokop is one of the villages in East Aceh which has a watershed in the Leuser Ecosystem. Human activities have the potential to disrupt the Trophic Status of Lokop River, such as the use of pesticides for agriculture, household waste and the use of potassium for fishing. It is necessary to research the quality of the waters in the Lokop River. The plankton community present in river waters can be an indicator of environmental pollution by analyzing the saprobic index. This study aims to determine the index of plankton diversity and water quality in the Leuser Ecosystem of the Lokop River through the saprobic index. The research was conducted at three stations. A sampling of plankton was taken in the form of a 10 cc filtrate and five replications were carried out for each study site. Water quality measurements include pH, TDS, Temperature, transparancy, depth, and current. 11 potential species can be used as pollution indicators in the Lokop River, namely Cladophora sp, Diatoma elongatum, Fragilaria capucina, Oedogonium sp., Gonatozygon sp, Lyngbya agardh, Melosira sp., Merismopedia punctata, Microspora sp, Pinnularia sp, Synedra ulna. The plankton diversity index is in the medium category. Based on the Saprobic Index, the level of pollution at the research site was not to lightly loaded of organic pollution and lowly loaded of organic pollution.Keywords:IsoprobikPlanktonBioindicatorLokop